Implementasi Digital Smart Care pada Kader Kesehatan sebagai Upaya Pencegahan Stunting - Annah Hubaedah; Yuni Khoirul Waroh; Anik Latifah (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2021)
This Community Service (PPM) was carried out in Siwalankerto Village, Wonocolo District, Surabaya Municipality with the title "Implementation of Digital Care for Health Cadres as Stunting Prevention Efforts", which aims to reduce the incidence of stunting by increasing knowledge and skills for the community, especially mothers. Toddlers, Posyandu Cadres, and PKK in Siwalankerto Urban Village through the use of Digital Care. From the results of the preliminary study, data on the number of toddlers in Siwalankerto in 2019, 1,010 people, 25 children with malnutrition. Seeing this condition, a solution is needed to overcome problems in toddlers, especially those related to stunting. The method used in this Community Service is the use of Digital Care. The targets are: toddler mothers, Posyandu cadres, and PKK in the Siwalankerto Village area. The hope of the results of PPM activities is to increase knowledge and skills in preventing stunting.